Online College Portal (International Journal of Current Engineering and Technology, 2015)
Online College Portal (OCP) provides a simple interface for maintenance of student–faculty information. It can be used by educational institutes or colleges to maintain the records of students easily. The creation and management of accurate, update information regarding a students’ academic career is critically important in the university as well as colleges. Student information system deals with all kind of student details, academic related reports, college details, course details, curriculum, batch details, placement details and other resource related details too. It tracks all the details of a student from the day one to the end of the course which can be used for all reporting, tracking of attendance, progress in the course, completed semesters, upcoming semester year curriculum details, exam details, project or any other assignment details, final exam result and all these will be available through a secure, online interface embedded in the college’s site . It will also have faculty details, batch execution details, students’ details in all aspects, the various academic notifications to the staff and students updated by the college administration [11]. It also facilitate us explore all the activities taking place in the college, different reports and queries are generated based on vast options related to students, batch, course, faculty, exams, semesters, certification and even for the entire college.
Keywords: Database; HTML; Online College Portal; SQL.